Hubungan Timbal Balik Manusia dan Alam dalam Legenda Ikan Bungo: Kajian Ekologi Sastra - Arisa; Muhlis; Andi Srimularahmah; Nur Rahmi (GERAM: Gerakan Aktif Menulis, 2021)
Literary ecology in the Bungo Fish legend discusses the relationship between humans and nature and vice versa. To create a balance, awareness is needed in managing, preserving and maintaining local wisdom, which is beginning to erode due to human unpreparedness in facing technological developments. The problems in literary works, especially the Bungo Fish legend originating from Sumpabaka in Wajo Regency, are based on several reasons. First, there is a relationship between living things and their environment experienced by the main character, namely Topanggalung and Bungo Fish. Second, the local colour is very thick in the legend of Bungo Fish, which is that the people who come from Sumpabaka do not consume Bungo Fish. Third, the problem of literary ecology in the Bungo Fish legend, if examined carefully, is social criticism of real life that does not pay attention to nature. This study discusses the reciprocal relationship between humans (characters) and nature based on literary ecology based on the problems above. This study describes the literary ecology related to the reciprocal relationship between humans and nature in the Bungo Fish legend. The method used in this research was a literature study that specifically examined the text on the Bungo Fish legend. The collected data analyzed by analytic descriptive and data analysis techniques. The results of research related to the reciprocal relationship between humans and nature include human responsibility towards nature, living in harmony with nature, being fair with nature, upholding democracy with nature, and moral integrity.